Effect of Acidic treatment on metal adsorptions of Sugarcane bagasse based Activated Carbon - Mohd Irfan Hatim, Mohamed Dzahir; Umi Fazara, Md. Ali (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti kejuruteraan Utara Malaysia (KUKUM), 15th June 2006 at DKG 4 & DKG 5, Kubang Gajah, Arau, Perlis.